Pemenuhan Hak Anak Penyandang Disabilitas Melalui Pendidikan Inklusif - Rizka Umar; Hijrah Lahaling; Rusmulyadi Rusmulyadi (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2025)
Undang-Undang Nomor 20 Tahun 2003 tentang Sistem Pendidikan Nasional dan Undang-Undang Nomor 8 Tahun 2016 tentang Penyandang Disabilitas affirming the obligation of the government and local governments to provide education for all citizens, including students with disabilities through special and inclusive education. This empirical research with a quantitative approach resulted in two main findings: Fulfillment of the rights of children with disabilities through inclusive education, including the facilitation of basic skills and the establishment of Disability Service Units; and Factors inhibiting the fulfilment of these rights in Gorontalo City include structural factors (ineffective policy implementation and infrastructure limitations) and institutional factors (lack of trained teachers and inflexible curriculum).